2022
DOI: 10.3390/ijms23137263
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Methods to Map In Vivo Changes of OXPHOS and Oxidative Stress in Neurodegenerative Disorders

Abstract: Mitochondrial dysfunction is a pathophysiological hallmark of most neurodegenerative diseases. Several clinical trials targeting mitochondrial dysfunction have been performed with conflicting results. Reliable biomarkers of mitochondrial dysfunction in vivo are thus needed to optimize future clinical trial designs. This narrative review highlights various neuroimaging methods to probe mitochondrial dysfunction. We provide a general overview of the current biological understanding of mitochondrial dysfunction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 171 publications
0
27
0
Order By: Relevance
“…This is likely due to many studies being limited by small sample sizes, as well as to differences in brain regions examined, metabolite outcome reporting, and imaging methodology [ 53 ]. Older studies were also limited by acquisitions performed at 1.5 Tesla with only surface coil localization and lower SNR than 3.0 Tesla, resulting in limited coverage and introduction of inhomogeneous spin excitation [ 54 ]. Generally, older 31 P-MRS reports on differences between AD patients and elderly controls provided mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to many studies being limited by small sample sizes, as well as to differences in brain regions examined, metabolite outcome reporting, and imaging methodology [ 53 ]. Older studies were also limited by acquisitions performed at 1.5 Tesla with only surface coil localization and lower SNR than 3.0 Tesla, resulting in limited coverage and introduction of inhomogeneous spin excitation [ 54 ]. Generally, older 31 P-MRS reports on differences between AD patients and elderly controls provided mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, older studies comparing generally small samples of AD patients and elderly controls reported contrasting results of elevated PCr 27 or ATP 28 , or no effects 29 , 45 . Such discrepancies are likely due to the fact that these studies were performed at 1.5 Tesla with only surface coil localization and lower SNR than 3.0 Tesla, which limited coverage and introduced inhomogeneous spin excitation 46 . Modern systems operating at 3 Tesla or higher, with volume or phased array coils, have allowed for improved 31 P-MRS coverage and sensitivity, which provides the opportunity to explore regional differences in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This previous assumption may have been reasonable because no correlations were shown between depleted HEP levels and LEDD 9,16 . However, our study illustrates that the treatment with L‐DOPA can substantially confound metabolic measurements in PwPD 11,17 …”
Section: Discussionmentioning
confidence: 62%
“…9,16 However, our study illustrates that the treatment with L-DOPA can substantially confound metabolic measurements in PwPD. 11,17 We demonstrated that exogenously administered L-DOPA strongly interferes with the energy metabolism of the basal ganglia independent of the PD state. The lack of treatment effects on the midbrain HEP levels suggests that the observed changes are likely limited to the site of L-DOPA action in the striatum.…”
Section: Discussionmentioning
confidence: 92%